2023
DOI: 10.3390/biomedicines11061653
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epicardial Adipose Tissue Secretome on Cardiovascular Diseases

Abstract: Obesity and insulin resistance are associated with the inflamed and defective adipose tissue (AT) phenotype, and are established risk factors for cardiovascular diseases (CVDs). Extracellular vesicles (EVs) are a heterogeneous group of cell-derived lipid membrane vesicles involved in the onset and development of many pathologies, including insulin resistance, diabetes, and CVDs. The inflammation associated with overweight and obesity triggers the transition of the AT secretome from healthy to pathological, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…The mechanism causing the difference between intraovarian injection and intravenous injection is not clear at this moment. It is known that metabolic aberrations, such as altered glucose levels and insulin resistance, are mainly regulated by adipose and liver tissue, not the ovary [ 53 , 54 , 55 ]. In our previous study, we found that locally injected MSCs did not migrate into other tissue, and the majority of injected cells stayed within injected tissue [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism causing the difference between intraovarian injection and intravenous injection is not clear at this moment. It is known that metabolic aberrations, such as altered glucose levels and insulin resistance, are mainly regulated by adipose and liver tissue, not the ovary [ 53 , 54 , 55 ]. In our previous study, we found that locally injected MSCs did not migrate into other tissue, and the majority of injected cells stayed within injected tissue [ 56 ].…”
Section: Discussionmentioning
confidence: 99%